When does Competition Mitigate Agency Problems? - TANG, Yuehua (Institutional Knowledge at Singapore Management University, 2005)
This paper examines empirically how the performance correlation of firms within an industry affects the degree to which product market competition mitigates agency problems. Using the passage of state anti-takeover laws as a source of identifying exogenous variation in corporate governance, I find that in homogeneous industries the effect of business combination (BC) laws on firms’ operating performance varies inversely with the level of competition, while in heterogeneous industries all firms experience a decline in operating performance, not varying with industry competition. I find similar results on stock prices when examining the stock market reactions of the first newspaper reports of BC laws. My results are also robust to the use of firm-level corporate governance measures (e.g. G-index). This study contributes to the literature by providing empirical evidence on the channel through which competition acts as a disciplinary mechanism.